2016
DOI: 10.3892/mmr.2016.5932
|View full text |Cite
|
Sign up to set email alerts
|

NLS-RARα modulates acute promyelocytic leukemia NB4 cell proliferation and differentiation via the PI3K/AKT pathway

Abstract: In patients with acute promyelocytic leukemia (APL), ~98% express the promyelocytic leukemia (PML)-retinoic acid receptor α (RARα) fusion protein. Previous studies have shown that, in primary leukemia cells of patients with APL, the cleavage of PML-RARα by neutrophil elastase is important for its ability to initiate APL. This cleavage separates the nuclear localization signal (NLS) from PML, leading to the formation of a novel protein, NLS-RARα, although its underlying mechanism in APL remains to be fully eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Normally, GSK activity is inhibited by AKT activation, but the activity of both AKT and GSK can be down-regulated under certain conditions. Song et al [58] demonstrated that a fusion protein NLS-RAR promoted both AKT and GSK-3β phosphorylation in NB4 cells (an acute promyelocytic leukemia cell line). The protein levels of both p-AKT and p-GSK-3β were decreased following pretreatment with the PI3K inhibitor LY294002 [58].…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Normally, GSK activity is inhibited by AKT activation, but the activity of both AKT and GSK can be down-regulated under certain conditions. Song et al [58] demonstrated that a fusion protein NLS-RAR promoted both AKT and GSK-3β phosphorylation in NB4 cells (an acute promyelocytic leukemia cell line). The protein levels of both p-AKT and p-GSK-3β were decreased following pretreatment with the PI3K inhibitor LY294002 [58].…”
Section: F I G U R Ementioning
confidence: 99%
“…Song et al [58] demonstrated that a fusion protein NLS-RAR promoted both AKT and GSK-3β phosphorylation in NB4 cells (an acute promyelocytic leukemia cell line). The protein levels of both p-AKT and p-GSK-3β were decreased following pretreatment with the PI3K inhibitor LY294002 [58]. Jordan et al [59] showed that myristoylated AKT blocked o-sulfated AGF function in a bladder cancer cell line, but up-regulated both p-AKT and p-GSK.…”
Section: F I G U R Ementioning
confidence: 99%
“…For detection of the cell differentiation antigen, CD11 antigen-like family member B was used (CD11b), after 72 h of treatment, the cells were collected (1x10 6 /group) and washed with three times with pre-cooled PBS, then incubated with phycoerythrin (PE) conjugated CD11b antibody (12011342; eBioscience, Inc., San Diego, CA, USA) at 4˚C for 30 min in the dark (32). The cells were then analyzed using flow cytometry (BD FACSVantage; BD Biosciences, San Jose, CA, USA) and CellQuest Pro software version 5.1 (BD Biosciences).…”
Section: Analyses Of Cell Differentiation Marker By Flow Cytometrymentioning
confidence: 99%